'Possibly they did not know themselves': the ambivalent government of sex and work in the Northern Territory Aboriginals Ordinance 1918. Issue 3 (3rd July 2017) - Silverstein, Ben
Abstract: The Aboriginals Ordinance of 1918 was the first piece of Commonwealth legislation to address the government of Aboriginal people. Covering the Northern Territory, it focused primarily on conditions in Darwin and operationalised Baldwin Spencer's understanding of the project and terrain of government. This article focuses on the confusion that attended its idiosyncratic definition of 'Aboriginal', arguing that its uncertainty was not a problem but a condition of its operation. The Ordinance was directed primarily towards securing a White Australia by fostering a healthy white tropical population, practising a settler colonial biopolitics of the population. In conceiving Aboriginal subjects as both domestic labourers providing an indispensable service to white family life in the tropics and as traffickers in venereal disease, threatening white health, the Ordinance registered an ambivalence fundamental to northern government that was perplexing to those who sought in it clarity. It aimed to secure a white population by exercising lawful eruptions of power over the intimate relationships and mobilities of all northern Aboriginal people, fabricating a racial taxonomy that was divided by a thick, contingent and discretionary colour line.